A real-time biphasic Kalman filter-based model for estimating human core temperature from heart rate measurements for application in the occupational field - Falcone, Tiziana; Del Ferraro, Simona; Molinaro, Vincenzo; Zollo, Loredana; Lenzuni, Paolo (Frontiers in Public Health, 2024)
Introduction Early identification of hypothermia or hyperthermia is of vital importance, and real-time monitoring of core temperature (CT) of the workers exposed to thermal environments is an extremely valuable tool. From the existing literature studies, the model developed by Buller et al. in their study of 2013 that generates real-time estimates of CT from heart rate (HR) measurements using the Kalman filter (KF) shows good potential for occupational application. However, some aspects could be improved to reliably handle the existing very wide range of workers and work activities. This study presents a real-time CT estimation model, called the Biphasic Kalman filter-based (BKFB) model, based on HR measurement, with characteristics suited to application in the occupational field. Methods Thirteen healthy subjects (six female and seven male) were included in the study to perform three consecutive tasks simulating work activities. During each test, an ingestible CT sensor was used to measure CT and a HR sensor to measure HR. The KF methodology was used to develop the BKFB model. Results An algorithm with a biphasic structure was developed using two different models for the increasing and decreasing phases of CT, with the ability to switch between the two based on an HR threshold. CT estimates were compared with CT measurements, and with respect to overall root mean square error (RMSE), the BKFB model achieved a sizeable reduction (0.28 ± 0.12°C) compared to the Buller et al. model (0.34 ± 0.16°C). Discussion The BKFB model introduced some modifications over the Buller et al. model for a more effective application in the occupational field. It was developed using data collected from a sample of workers (heavily weighted toward middle-aged, not very fit, and with a considerable fraction of female workers), and it also included two different modeling of CT (for the up- and down-phases), which allowed for better behavioral modeling in the two different stages. The BKFB model provides CT estimates reasonably in comparison to the measured intra-abdominal temperature values in both the activity and recovery phases but is more practical and easier to use for a real-time monitoring system of the workers' thermal states.